Enhancing Farmers' Capacity in the Karya Manunggal Livestock Group, Donokerto, Turi, Sleman, Yogyakarta, through Comparative Analysis of Different Type of Silo for Fermented Complete Feed Production - Aji Praba Baskara; Moh Sofi'ul Anam; Ali Agus; Erif Maha Nugraha Setyawan; Najmu Tsaqib Akhda; Muhammad Maulana Sadid; Abdul Hafidz Ihtiarta (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2026)
The increasing demand for animal protein requires improvements in livestock production. Feed accounts for the largest proportion of farm operational costs. The use of fermented complete feed can help optimize farm productivity. The Faculty of Animal Science, Universitas Gadjah Mada (UGM), actively supports livestock productivity through a community service program based on the application of Teknologi Tepat Guna (Appropriate Technology), with a focus on fermented complete feed production techniques. This community service program aimed to improve farmers’ capacity to produce fermented feed by comparing different types of silos. The Karya Manunggal Livestock Group in Sleman, which faces challenges in maintaining feed quality and ensuring a sustainable feed supply, was selected as the program partner. Four types of silos were evaluated, namely bunker silos, plastic drums, plastic bags, and jumbo bags, to identify the most effective medium for producing high-quality fermented feed. The results showed that drum silos and plastic bags produced feed with better physical quality, aroma, pH, and palatability than the other silo types. The drum silo was identified as the best option for maintaining fermentation quality, whereas the jumbo bag showed the greatest cost efficiency. This program successfully provided practical guidance for farmers in selecting appropriate silos according to local needs and conditions. Through this program, farmers’ productivity is expected to improve through the adoption of effective fermentation technology.